The Effect of Product Market Competition on the Relationship between Capital Structure and Financial Performance of Companies - Mahmoud Mahmoudzadeh; Ali Seyfi (International Journal of Economics and Financial Issues, 2017)
Investors and stakeholders are the two groups to which information about the company's financial performance is important. Given the importance of good financial performance of the companies to investors and stakeholders for maximizing their wealth, it is essential to identify and study the factors affecting financial performance. Therefore, the present study aims to examine the effect of product market competition on the relationship between capital structure and financial performance of the companies listed in Tehran Stock Exchange during 2009 to 2013. Panel data model and Eviews software were used for data analysis and hypotheses test. General conclusion of the research hypotheses shows that financial leverage, level of competition, and mutual effect of financial leverage have significant effect on the sample companies’ financial performance. Thus, all research hypotheses are confirmed.